Association of endostatin with mortality in patients with chronic heart failure. (28th November 2013) - Gouya, Ghazaleh; Siller‐Matula, Jolanta M.; Fritzer‐Szekeres, Monika; Neuhold, Stephanie; Storka, Angela; Neuhofer, Lisa M.; Clodi, Martin; Hülsmann, Martin; Pacher, Richard; Wolzt, Michael
Abstract Background Experimental data imply that in decompensated heart failure (HF), the anti‐angiogenic factor endostatin is increased. This study aimed to investigate whether the angiogenesis inhibitor endostatin is related to the risk of all‐cause mortality in a prospective cohort study of chronic HF patients. Methods In this prospective observational cohort study, endostatin serum concentrations were determined in patients with chronic HF. Mortality data were recorded during a median follow‐up of 31 months. Results One fifty one patients were included. The overall mortality rate was 20%. Baseline endostatin concentrations > 245 ng/mL were associated with higher risk of all‐cause mortality [HR 8·7 (95% CI 2·5–30·0); P = 0·001] in the multivariate analysis as compared to endostatin concentrations ≤ 245 ng/mL. When both endostatin and NT‐proBNP were above the calculated cut‐off of 245 ng/mL and 2386 pg/mL, respectively, the prognostic utility of both biomarkers increased [HR 40·8 (95% CI 4·7–354·6); P = 0·001] compared with values lower than the cut‐offs. Conclusions Serum endostatin concentrations are independently associated with all‐cause mortality. Furthermore, combination of endostatin and NT‐proBNP discriminates patients at high risk.